Lasers for the observation of multiple order nuclear reactions - Burggraf, Jeffrey; Zylstra, Alex (Frontiers in Physics, 2022)
Nuclear reaction rates become nonlinear with respect to flux (1/cm2/s) in extreme environments such as those found during stellar nucleosynthesis and terrestrial nuclear detonations. To observe these effects directly in the laboratory, extremely high particle fluences (1/cm2) are necessary but not sufficient. Reactor-based neutron sources, such as the Institut Laue-Langevin's high-flux neutron reactor, were previously the closest to meeting this challenge, albeit over hour time scales. In ultra-high flux environments, where multiple reactions occur on picosecond time scales, nuclei are unable to return to their ground states between reactions; consequently, reactions take place on excited nuclei. To accurately model high-flux environments, data on the cross-sections of excited nuclear states are required, which differ significantly from those of ground states due to spin/parity effects. In order to replicate these effects in the laboratory, short high-fluence pulses on the order of the lifetime of a typical nuclear excited state (generally <1 ns) are required. Particle beams generated by high-intensity lasers are uniquely positioned to meet this need with the potential to produce fluences of 10^17 protons per cm2 and 10^22 neutrons per cm2 over a few pico-seconds or less. In addition to providing a quantitative analysis of the rates of multiple rapid reactions in general, the present work examines a number of laser-based experiments that could be conducted in the near future to observe multiple rapid reactions for laboratory-based astrophysics and the measurement of exotic cross-sections.